THE EFFECTIVENESS OF ACUPRESSURE AND PELVIC ROCKING EXERCISE IN REDUCING DYSMENORRHEA PAIN INTENSITY AMONG ADOLESCENT GIRLS - Een Nuraenah; Wahyudin Rajab; Syarifah Syarifah; Uswatul Chasanah; Niki Rian Putri; Istiaanah Wahyuningsih; Jujun Dwi Astuti (Jurusan Kebidanan Poltekkes Kemenkes Jakarta I, 2026)
Dysmenorrhea is a common gynecological condition affecting adolescents and women of reproductive age, with a prevalence ranging from 1.7% to 97% as reported by the World Health Organization (WHO). Non-pharmacological interventions, such as acupressure and pelvic rocking exercise, have been shown to reduce dysmenorrheal pain intensity. This study aimed to compare the effectiveness of acupressure and pelvic rocking exercise in reducing dysmenorrheal pain intensity among adolescent girls. A quasi-experimental study with a pretest–posttest design was conducted involving 64 respondents selected through random sampling based on predefined inclusion and exclusion criteria. Pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed using paired sample t-tests and independent sample t-tests. The results demonstrated that both acupressure and pelvic rocking exercise significantly reduced dysmenorrheal pain intensity (?<0.001). However, no statistically significant difference was found between the two interventions (? = 0.531; ?> 0.05). In conclusion, both acupressure and pelvic rocking exercise are effective in reducing dysmenorrheal pain intensity; however, neither intervention demonstrated superior effectiveness over the other.